The history of mine surveying and mining maps - Ovesná, Gabriela; Staňková, Hana; Plánka, Ladislav; Wlochová, Andrea (Geodesy and Cartography, 2017)
The beginnings of the mining history date back to ancient times, up to the second century B.C. One field closely related to mining activities is mine surveying. Mine surveying and mapping are disciplines that deal with the surveying and displaying of underground works and mining claims, in which their spatial relationships are determined against the surface.The introductory part of the paper is dedicated to the history and development of the mine surveying discipline and mapping, and to the profession of a mine surveyor. The second part of the article is devoted to historical mining maps produced in Austria, the Czech Republic and Slovakia. Historical mine maps belong to the significant treasures of past times, and from today's perspective they are often considered to be pieces of art. In the time of their origin they belonged to the most sophisticated technical-natural documents that were used for the registration of property rights, and for the performance of mining activities. With regard to the period in which they were created they are accurate, yet there are few records on their history.